An experiential pathway to fintech: An extended UTAUT2 analysis of technology adoption among indigenous Malaysian MSMEs - Faiz, Azizul; Fernando, Yudi; Faris, Azizul (HBZ & Partners PLT, 2025)
This study investigates potential FinTech product adoption for Indigenous (Bumiputera) Micro, Small, and Medium Enterprises (MSMEs). Technology adoption research often overlooks differences within entrepreneurial communities and this study fills that gap with Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model application. Results shown the Bumiputera MSMEs' desire to adopt this potential FinTech is shaped by UTAUT2 (Hedonic Motivation, Performance Expectancy and Facilitating Conditions) factors. Other UTAUT2 (Effort Expectancy and Price Value) factors were significant but weaker results. Social Influence was not a predictor factor. These findings challenge a uniform approach to FinTech development and offer guidance for stakeholders and Fintech service providers to create inclusive financial tools and help close the MSME financing gap.